Harmonic Mean Cordial Labeling of One Chord Cn V G - Gandhi, Harsh; Parejiya, Jaydeep; Jariya, M M; Solanki, Ramesh (International Journal of Membrane Science and Technology, 2023)
All the graphs considered in this article are simple and undirected. Let G = (V (G),E(G)) be a simple undirected graph. A function is called Harmonic Mean Cordial if the induced function defined by satisfies the condition and for any , where and denote the number of vertices and number of edges with label respectively and denotes the greatest integer less than or equals to . A graph is called a harmonic mean cordial graph if it admits harmonic mean cordial labeling. In this article, we have discussed the harmonic mean cordial labeling of One Chord .